Pathological correlations of [F‐18]‐AV‐1451 imaging in non‐alzheimer tauopathies. Issue 1 (24th January 2017) - Marquié, Marta; Normandin, Marc D.; Meltzer, Avery C.; Siao Tick Chong, Michael; Andrea, Nicolas V.; Antón‐Fernández, Alejandro; Klunk, William E.; Mathis, Chester A.; Ikonomovic, Milos D.; Debnath, Manik; Bien, Elizabeth A.; Vanderburg, Charles R.; et al.
Abstract : Objective: Recent studies have shown that positron emission tomography (PET) tracer AV‐1451 exhibits high binding affinity for paired helical filament (PHF)‐tau pathology in Alzheimer's brains. However, the ability of this ligand to bind to tau lesions in other tauopathies remains controversial. Our goal was to examine the correlation of in vivo and postmortem AV‐1451 binding patterns in three autopsy‐confirmed non‐Alzheimer tauopathy cases. Methods: We quantified in vivo retention of [F‐18]‐AV‐1451 and performed autoradiography, [H‐3]‐AV‐1451 binding assays, and quantitative tau measurements in postmortem brain samples from two progressive supranuclear palsy (PSP) cases and a MAPT P301L mutation carrier. They all underwent [F‐18]‐AV‐1451 PET imaging before death. Results: The three subjects exhibited [F‐18]‐AV‐1451 in vivo retention predominantly in basal ganglia and midbrain. Neuropathological examination confirmed the PSP diagnosis in the first two subjects; the MAPT P301L mutation carrier had an atypical tauopathy characterized by grain‐like tau‐containing neurites in gray and white matter with heaviest burden in basal ganglia. In all three cases, autoradiography failed to show detectable [F‐18]‐AV‐1451 binding in multiple brain regions examined, with the exception of entorhinal cortex (reflecting incidental age‐related neurofibrillary tangles) and neuromelanin‐containing neurons in the substantia nigra (off‐target binding). The lack of a consistent significant correlation between in vivo [F‐18]‐AV‐1541 retention and postmortem in vitro binding and tau measures in these cases suggests that this ligand has low affinity for tau lesions primarily made of straight tau filaments. Interpretation: AV‐1451 may have limited utility for in vivo selective and reliable detection of tau aggregates in these non‐Alzheimer tauopathies. ANN NEUROL 2017;81:117–128